Pembangunan Sistem Informasi Rawat Jalan Berbasis Web dengan Fitur Mobile pada Puskesmas Tarok Kota Payakumbuh - Dini Hariyati; Ricky Akbar; Meza Silvana (Jurnal Nasional Teknologi dan Sistem Informasi, 2017)
The Center for Public Health (Puskesmas) serves as the primary health service center in outpatient services. One of them is Tarok Puskesmas which is one of the public health centers in Payakumbuh. Currently the outpatient service system in Tarok Puskesmas is still done manually so that there is often a long process of information exchange or the occurrence of misinformation between sections in the puskesmas. Therefore, an application is required to improve the system by designing and building a web-based information system using mobile features. Development methods on this system use waterfall method and application testing using blackbox testing method. The system is designed by analyzing the needs of the current system with three functionalities, ie viewing the history of patient visits, viewing medical records, and viewing reports of puskesmas that can be described by contex diagrams in seven entities, ie patients, admissions officers, policemen, pharmacists, Doctors, and leaders. This app is designed using a PostgreSQL database. This outpatient information system database has eleven tables, ie patient table, visit table, traffic_transaction table, family_name table, drug table, employee table, access table, poly table, disease table, preset table, and transaction table. The test results show that the implementation results have been in accordance with the functional requirements of system applications.